Frequency of Hyponatremia in Patients With Decompensated Chronic Liver Disease Presenting at Tertiary Care Hospital - Bibi, Aisha; Khan, Wasil; Asim, Muhammad; Hilal, Maria; Hazrat, Irum; Abdullah, . (Biological and Clinical Sciences Research Journal, 2025)
Hyponatremia is a frequent electrolyte disturbance in decompensated chronic liver disease and is linked with worse clinical outcomes. Local estimates help guide early detection and supportive management in tertiary-care settings. Objective: To determine the frequency of hyponatremia in patients with decompensated chronic liver disease presenting at tertiary care hospital. Methods: This study was conducted on 86 patients diagnosed with decompensated chronic liver disease, determined on abdominal ultrasound as coarse parenchymal echogenicity, irregular margins, and ascites, along with complaints such as Fever (>101°F or 38.3°C), abdominal pain (VAS > 3), and fatigue. Patients with flapping tremors and cardiac diseases were excluded. Hyponatremia was assessed in all patients, defined as serum sodium level < 130 mmol/L. SPSS 25 was used for analysis. Results: In the present study, the mean age of the patients was 53.06 ± 13.69 years, gender wise males were in majority 60 (69.8%). Mean serum sodium level was 134.51 ± 7.21 mmol/L. Hyponatremia was observed in 26 patients (30.2%). Conclusion: Hyponatremia is a significant complication in the patients with decompensated chronic liver disease, it was present in 30.2% patients.